A Case of Acute Budd-Chiari Syndrome Complicating Primary Antiphospholipid Syndrome Presenting as Acute Abdomen and Responding to Tight Anticoagulant Therapy - Naofumi Chinen; Yasushi Koyama; Shinji Sato; Yasuo Suzuki (Case Reports in Rheumatology)
A 34-year-old woman with primary antiphospholipid syndrome was admitted to the Gastroenterology Department of our hospital with fever, acute abdomen, watery diarrhea, and extremely high levels of inflammatory parameters. She had a history of left lower limb deep vein thrombosis and pulmonary embolism and was taking warfarin potassium. Acute gastroenteritis was suspected and an antibiotic was administered, but symptoms progressed. Abdominal ultrasonography showed occlusion of the left hepatic vein and the middle hepatic vein and her D-dimer level was high. Accordingly, Budd-Chiari syndrome was diagnosed and high-dose intravenous infusion of heparin was initiated. Her abdominal symptoms improved and the levels of inflammatory parameters and D-dimer decreased rapidly. It is known that antiphospholipid syndrome can be complicated by Budd-Chiari syndrome that usually occurs as subacute or chronic onset, but acute onset is rare. It is difficult to diagnose acute Budd-Chiari syndrome complicating antiphospholipid syndrome and this complication generally has a poor outcome. However, the present case can get early diagnosis and successful treatment with tight anticoagulant therapy.